2011
DOI: 10.1038/cr.2011.71
|View full text |Cite
|
Sign up to set email alerts
|

Modulations of hMOF autoacetylation by SIRT1 regulate hMOF recruitment and activities on the chromatin

Abstract: A wide variety of nuclear regulators and enzymes are subjected to acetylation of the lysine residue, which regulates different aspects of protein functions. The MYST family histone acetyltransferase, human ortholog of MOF (hMOF), plays critical roles in transcription activation by acetylating nucleosomal H4K16. In this study, we found that hMOF acetylates itself in vitro and in vivo, and the acetylation is restricted to the conserved MYST domain (C2HC zinc finger and HAT), of which the K274 residue is the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 47 publications
8
64
0
Order By: Relevance
“…We extracted all of the lysine N-acetyltransferases identified in our data set ( Table I) and discovered that acetylation levels of the MYST acetyltransferase family were most affected by SIRT1 knockout. This result is in agreement with previous findings that Kat5 (Tip60) and Kat8 (Myst1), two of the MYST family proteins, are SIRT1 substrates that are negatively regulated by SIRT1 (33)(34)(35)(36). Moreover, we showed that Ing3, a known member of Kat7 (Myst2) protein complex, demonstrates an over 10-fold increase in acetylation level at two sites (K181, K264) in SIRT1 knockout cells.…”
Section: Analysis Of Dynamics In Protein Domains By Sirt1supporting
confidence: 82%
“…We extracted all of the lysine N-acetyltransferases identified in our data set ( Table I) and discovered that acetylation levels of the MYST acetyltransferase family were most affected by SIRT1 knockout. This result is in agreement with previous findings that Kat5 (Tip60) and Kat8 (Myst1), two of the MYST family proteins, are SIRT1 substrates that are negatively regulated by SIRT1 (33)(34)(35)(36). Moreover, we showed that Ing3, a known member of Kat7 (Myst2) protein complex, demonstrates an over 10-fold increase in acetylation level at two sites (K181, K264) in SIRT1 knockout cells.…”
Section: Analysis Of Dynamics In Protein Domains By Sirt1supporting
confidence: 82%
“…Recently the Akhtar and Liu groups also report that hMOF can be autoacetylated at Lys274 [5,8]. Compared with their studies, our work reveals that hMOF is autoacetylated in an intra-molecular manner, indicates that the autoacetylation of hMOF at Lys274 has a significant impact on the catalytic activity of the enzyme, and provides the structural basis for the modulation of the enzymatic activity by Lys274 acetylation.…”
mentioning
confidence: 58%
“…The closest mammalian Sir2 ortholog, Sirt1, is further involved in the transcriptional regulation of several key developmental regulators (Calvanese et al, 2010;Haigis and Sinclair, 2010;Lu et al, 2011) and was reported to associate with the stem cell-specific Polycomb group (PcG) repressive complex PRC4, preferentially under conditions of oxidative stress (Kuzmichev et al, 2005;O'Hagan et al, 2011). Consistent with a role for Sirt1 in stem cell homeostasis, Sirt1-deficient embryonic stem (ES) cells show increased sensitivity to oxidative stress, DNA damage accumulation, and genomic instability (Oberdoerffer et al, 2008; cues (Narala et al, 2008;Leko et al, 2012;Matsui et al, 2012;Peled et al, 2012).…”
mentioning
confidence: 83%